Antidiabetic Potential of Hylocereus Polyrhizus and Hylocereus Megalanthus Fruit Peel: An In vitro Study - Fahad Saad. Alhodieb (Journal of Pharmacy and Bioallied Sciences)
Background: Diabetes is a chronic metabolic condition affecting mainly carbohydrate metabolism. Dragon fruit is a commonly consumed fruit in Asia-pacific countries, with reported anti-diabetic potential. Objectives: The presents study explores the use of dragon fruit peel as an anti-diabetic supplement. Materials And Method: Fruit peels from two varieties (Red and Yellow) were evaluated for their ability to absorb glucose, inhibit glucose diffusion, and inhibit starch digestion using in vitro models. Result: Both red and yellow dragon fruit peel powder samples decreased starch digestion significantly compared to wheat bran and inhibited glucose diffusion, as indicated by the glucose dialysis retardation index (GDRI) values. Conclusion: The findings of the study indicate that both red and yellow dragon fruit peel possesses significant antidiabetic potential.